Engendering the state family, work, and welfare in Canada - Christie, Nancy 1958- (Univ. of Toronto Press, 2000)
"The author's explanation of gender's role in the conception of modern Canadian welfare policy takes current scholarship into novel territory. Her analyses of the perspectives of maternal feminists, clergymen, organized labour, businessmen, university social scientists, welfare administrators, social workers, and government policy makers are fascinating to read and contribute greatly to our understanding of the current debates in welfare policy making."--BOOK JACKET.